2011
DOI: 10.1007/s00425-011-1444-6
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal localisation of the final steps of the mevalonic acid pathway in planta

Abstract: In plants, the mevalonic acid (MVA) pathway provides precursors for the formation of triterpenes, sesquiterpenes, phytosterols and primary metabolites important for cell integrity. Here, we have cloned the cDNA encoding enzymes catalysing the final three steps of the MVA pathway from Madagascar periwinkle (Catharanthus roseus), mevalonate kinase (MVK), 5-phosphomevalonate kinase (PMK) and mevalonate 5-diphosphate decarboxylase (MVD). These cDNA were shown to functionally complement MVA pathway deletion mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 45 publications
4
75
0
Order By: Relevance
“…Besides plastids and the endoplasmic reticulum, postulated earlier to harbor CPTs (Skorupinska-Tudek et al, 2008), plant peroxisomes also could possess their own CPT, as was observed in mammals and yeast (Ericsson et al, 1992;Skoneczny et al, 2006). Moreover, the existence of the peroxisomal pathway converting MVA to IPP in mammals and plants (Thompson et al, 1987;Simkin et al, 2011) further supports this concept. Still, the type of all-trans-initiator involved in the biosynthesis of Dols in Arabidopsis roots remains enigmatic.…”
Section: Discussionmentioning
confidence: 74%
“…Besides plastids and the endoplasmic reticulum, postulated earlier to harbor CPTs (Skorupinska-Tudek et al, 2008), plant peroxisomes also could possess their own CPT, as was observed in mammals and yeast (Ericsson et al, 1992;Skoneczny et al, 2006). Moreover, the existence of the peroxisomal pathway converting MVA to IPP in mammals and plants (Thompson et al, 1987;Simkin et al, 2011) further supports this concept. Still, the type of all-trans-initiator involved in the biosynthesis of Dols in Arabidopsis roots remains enigmatic.…”
Section: Discussionmentioning
confidence: 74%
“…The last two MVA pathway enzymes, PMK and MDD, as well as isopentenyl diphosphate isomerase (IDI), catalyzing the interconversion of IPP and DMAPP, are localized in peroxisomes (16,17). To determine the site of IPK action, we established its subcellular localization.…”
Section: Ipk Is Coexpressed With the Mva Pathway And Downstream Terpementioning
confidence: 99%
“…In this addendum, we provide additional data describing the peroxisomal localization of 5-phosphomevalonate kinase and mevalonate 5-diphosphate decarboxylase, the last two enzymes of the mevalonic acid pathway leading to IPP. 2 This finding was reinforced in our latest report showing that a short isoform of farnesyl diphosphate, using IPP and DMAPP as substrates, is also targeted to the organelle. 3 Therefore, the classical sequestration of isoprenoid biosynthesis between plastids and cytosol/ER can be revisited by including the peroxisome as an additional isoprenoid biosynthetic compartment within plant cells.…”
mentioning
confidence: 82%
“…Thus, transient transformations of Madagascar periwinkle (Catharanthus roseus) cells with Yellow Fluorescent Protein-fused constructs revealed that the last two enzymes of the MVA pathway from Arabidopsis and C. roseus, 5-phosphomevalonate kinase (PMK) and mevalonate 5-diphosphate decarboxylase (MVD), are localized to peroxisomes. 2 Furthermore, two other C. roseus enzymes related to the MVA pathway have been shown to be targeted to this organelle: a short isoform of IDI (Courdavault, personal communication), secondary metabolite paxilline, is also targeted to the peroxisome. 9 In plants, recent studies have identified the peroxisome as an additional site for isoprenoid biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation